Outreach on Heart-Healthy Exercise and Industry Training Based on Local Wisdom Toward a Healthy and Prosperous Community in Line with the Sustainable Development Goals (SDGs) in Kenagarian Maek - Anggun Permata Sari; Nugroho Susanto; Shinta Sari; Rara Putri Maliza; Anggi Yusriana; Dio Septiyan Helmi; Rina Mayangsari (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Coronary heart disease is one of the major health issues in the Maek Sub-district, driven by low levels of physical activity, limited public knowledge about disease prevention, and underutilization of local resources such as gambir plants. These conditions have led to an increase in cases of degenerative diseases and low community well-being. This community service program aims to improve public health through the promotion of healthy heart exercises and to empower the local economy through training in gambir processing based on local knowledge. Implementation methods include health education, healthy heart exercise sessions led by certified instructors, as well as industrial training and demonstrations of simple technologies for gambir processing to add value. The results of the activities demonstrate an increase in community knowledge regarding the importance of physical activity, the formation of healthy heart exercise communities, and improved skills in processing gambir into economically valuable products. Discussions indicate that the integration of health education and local economic empowerment not only enhances awareness and healthy lifestyle behaviors but also strengthens the community’s economic potential in a sustainable manner. Overall, this program contributes to the achievement of the Sustainable Development Goals (SDGs) through improved health outcomes, economic growth, and the optimization of local resources